Pengaruh Kadar Air Terhadap Modulus Elastisitas Beton Menggunakan Uji Ultrasonik - Neri Puspita Sari; Desi Yasri (Sekolah Tinggi Teknologi Pekanbaru, 2023)
The study was conducted to determine the effect of increasing the water content of 2.5%, 5%, 7.5% and 10% of the effect of adding water-cement ratio to the modulus of elasticity of concrete with the Ultrasonic Pulse Velocity/ UPV test. This research was carried out using fine aggregate type 1 sand from Cimalaka, maximum diameter of coarse aggregate 20 mm from Cimahi and Portland cement Type 1. Each test uses two samples. The results of the analysis show that the addition of water will reduce the value of the modulus of elasticity.